2019
DOI: 10.1002/jgh3.12258
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of chloroquine plus prednisone for the treatment of autoimmune hepatitis in a randomized trial

Abstract: Background and Aim Standard treatment for autoimmune hepatitis (AIH) consists of predniso(lo)ne and azathioprine. However, alternative therapy is required for non‐ or partial responders and in cases of side effects. The aim of this study was to evaluate the treatment outcomes associated with chloroquine plus prednisone in AIH patients. Methods Fifty‐seven patients were recruited to receive either azathioprine or chloroquine, both with prednisone, in a randomized trial. The primary end‐point was complete remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…In a sample of AIH patients (88.5% female, mean age = 37.54), Falcão et al 26 evaluated treatment outcomes associated with CQ plus prednisone and azathioprine plus prednisone. In this small sample size (overall N = 57; CQ + prednisone = 26), no patient developed psychosis after CQ ingestion, and 1 patient developed neuropathy as a consequence of the medication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sample of AIH patients (88.5% female, mean age = 37.54), Falcão et al 26 evaluated treatment outcomes associated with CQ plus prednisone and azathioprine plus prednisone. In this small sample size (overall N = 57; CQ + prednisone = 26), no patient developed psychosis after CQ ingestion, and 1 patient developed neuropathy as a consequence of the medication.…”
Section: Resultsmentioning
confidence: 99%
“…Most populational studies do not specify the dose in which individuals ingested CQ, especially survey-based and retrospective studies. The studies that addressed how much CQ was ingested reported a mean of 443 mg, ranging from 250 to 2700 mg. 7,11,16,19,26,39,80 Ursing et al 20 and Saint-Gerons et al 40 reported a more detailed dose, in which patients took 10 mg/kg on days 0 and 1 and 2 doses of 5 mg/kg on day 2, and 10 mg/kg on day 1 and 7.5 mg/kg on days 2 and 3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce relapse rates after treatment withdrawal, a randomized, double‐blind, 3‐year study with 250 mg/day chloroquine diphosphate versus placebo showed significant differences between the two groups. In this study, the features associated with reduced risk for AIH relapse were the anti‐SLA/LP seronegativity and chloroquine use . In another study to evaluate the role of chloroquine in association with prednisone (Pred) to induce a complete treatment response, the results showed its potential effects in the initial therapeutic regimen for the induction of remission …”
Section: Special Features Of Aih In South Americamentioning
confidence: 85%
“…Chloroquine and its derivatives have not only an enormous impact on the treatment of coronaviruses [ 53 , 55 , 59 , 64 ] (see the previous section), but are also effective against several others viruses in vitro, including: (i) human immunodeficiency virus (HIV) [ 95 , 96 , 97 , 98 , 99 , 100 , 101 ], (ii) hepatitis A (HAV) [ 102 ], B (HBV) [ 103 ], C (HCV) [ 104 ] viruses and autoimmune hepatitis [ 105 ], (iii) poliovirus [ 106 ], (iv) influenza A [ 107 , 108 ], B [ 109 ] and H5N1 [ 110 ] viruses, (v) Zika virus (ZIKV) [ 111 , 112 , 113 ], (vi) Ebola virus (EBOV) [ 114 ], (vii) Crimean–Congo hemorrhagic fever virus (CCHFV) [ 115 ], (viii) rabies virus [ 116 ], (ix) Chikungunya virus (CHIKV) [ 117 , 118 ], (x) Dengue virus (DENV) [ 119 , 120 , 121 ], (xi) Hendra, Nipah viruses [ 122 ], and (xii) herpes simplex virus (HSV) [ 123 ]. In this section, we briefly discuss the possible “non-Zn(II)-based” modes of action (if known) of chloroquine and hydroxychloroquine.…”
Section: Antiviral Properties Of Chloroquine and Hydroxychloroquinmentioning
confidence: 99%